2019
DOI: 10.2903/j.efsa.2019.5945
|View full text |Cite
|
Sign up to set email alerts
|

Annual Report on surveillance for avian influenza in poultry and wild birds in Member States of the European Union in 2018

Abstract: Avian influenza (AI) is a viral infectious disease that affects all species of domestic and wild birds. The viruses causing this disease can be of high (HPAI) or low (LPAI) pathogenicity and represent a continuous threat to poultry in Europe. Council Directive 2005/94/EC requests EU Member States (MSs) to carry out surveillance in poultry and wild birds and notify the results to the responsible authority. Therefore, MSs and Switzerland have implemented surveillance programmes to yearly monitor incursions of AI… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
15
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 12 publications
(15 citation statements)
references
References 13 publications
0
15
0
Order By: Relevance
“…Highly pathogenic avian influenza viruses (HPAIVs) of the Goose/Guangdong (Gs/Gd) lineage are an emerging threat to wild birds ( 1 11 ). Since the emergence of the H5 A/goose/Guangdong/1/96 lineage in 1996, HPAIVs have successfully adapted and circulated widely in several wild bird species ( 3 , 8 ).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Highly pathogenic avian influenza viruses (HPAIVs) of the Goose/Guangdong (Gs/Gd) lineage are an emerging threat to wild birds ( 1 11 ). Since the emergence of the H5 A/goose/Guangdong/1/96 lineage in 1996, HPAIVs have successfully adapted and circulated widely in several wild bird species ( 3 , 8 ).…”
Section: Introductionmentioning
confidence: 99%
“…Examples of these successful mechanisms are the numerous global incursions of the subtype H5N8, clade 2.3.4.4, in the 2014–2015, 2016–2017, and 2020–2021 seasons, which to date is responsible for the highest number of HPAIV outbreaks in wild birds. During the H5N8 outbreak in 2014–2015, the virus spread long distances from Asia to Europe and North America via infected migratory birds ( 1 , 2 , 6 ). Epidemiological analysis and experimental infection studies showed that wild ducks (including Eurasian wigeons, Anas penelope , and mallards, Anas platyrhynchos ) can be infected with 2014 H5N8 virus without clinical or pathological evidence of disease ( 13 20 ).…”
Section: Introductionmentioning
confidence: 99%
“…The risk of outbreaks in commercial poultry has increased in recent years, due to circulation of HPAI H5 viruses in the wild bird population (European Food Safety Authority et al, 2019). Furthermore, the expansion of free-range poultry farms, driven by consumers and animal welfare organizations, increases the opportunities for contact between poultry and wild birds (Bouwstra et al, 2017;Elbers & Gonzales, 2019).…”
Section: Introductionmentioning
confidence: 99%
“…Such a tool has several applications. First of all, EU countries monitor the circulation of AIV in their environment using dead wild bird surveillance programs (25). In such a surveillance, dead found wild birds are examined for AIV: AIV positive dead wild birds indicate that the virus may be circulating in the area where the bird was found.…”
Section: Introductionmentioning
confidence: 99%